Metal uptake in chicken giblets and human health implications - Chijioke, N. O.; Khandaker, Mayeen Uddin *; Tikpangi, K. M.; Bradley, D.A. * (Elsevier, 2020)
Recognizing the global concerns about metal contamination in food chain coupled with the high rate of consumption of chicken products as a major component of daily diet to humans, the presence of 14 metals (Fe, Cu, Mg, Zn, Al, Hg, Cd, As, Pb, Se, Ni, Sr, Cr and Sb) due to their persistence in our environment and food chain were determined in poultry chicken giblets to assess the potential non-carcinogenic and carcinogenic risks to human health. In general, essential elements such as Mg, Fe show higher concentrations than the potentially toxic metals. Statistical analysis indicates the latter to have similar origin and/or similar feedstuffs, consistent with the wide spread use of Cu and Zn as feed supplements in intensive poultry farming. The daily intake of the studied metals by the Malaysian population showed to be below the permissible levels of dietary intake set by various international organizations. Estimated non-carcinogenic risk due to all of the metals in the giblets show a value of 0.51 indicating the giblets to be safe for consumption at the current intake level. However, the carcinogenic risk resulting from toxic metals show slightly higher values than the US-EPA reference limit of 10−4. The results may not be thought to be of concern given the fact that chicken giblets form only a very minor part of dietary habit. However, considering the non-degradability of toxic metals and their potential accumulation in animal tissues, reduction in metal supplementation in animal feed should be introduced and periodic monitoring of chicken giblets may help to mitigate non-essential metal toxicity to public health.